Virginity Discourse in the Curse of Beauty’s Indah Hanaco - Fiqih Aisyatul Farokhah (Universitas Islam Negeri Imam Bonjol Padang, 2019)
This study aims to examine the discourse of virginity represented in Indah Hanaco’s The Curse of Beauty. Sales Promotion Girl (SPG) is one of the professions that are in great demand by women, especially teenagers today. SPG is a woman who has met certain criteria recruited by companies to promote, market and inform consumers of the products. Their work is vulnerable to sexual oppression. This inspired Indah Hanaco in writing her novel. Therefore, there are several issues to be discussed. (1) the form of virginity discourse represented by The Curse of Beauty. (2) the function of virginity discourse in The Curse of Beauty (3) the meaning of virginity discourse represented by Indah Hanaco. This study uses the analysis of form, function, meaning the discourse theory of Michel Foucault. This research shows, virginity is a discourse formed by the social construction of society about women who have never had sexual relations. The form of the discourse of virginity is shown through the story of the taboo of sexual intercourse before marriage or the importance of keeping the chastity (virginity) of women from sex intercourse with a lover. The function of virginity discourse in the novel is as a description of social construction in society about what is a woman's virginity. The meaning of the discourse of virginity represented by Indah Hanaco is that virginity is not a matter of the dignity of women but a matter of oppression of women in this case experienced by the SPG.